1973
DOI: 10.2135/cropsci1973.0011183x001300050017x
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Several Temperate Grasses Grown with Alfalfa and Harvested Two, Three, or Four Times Annually at Two Stubble Heights1

Abstract: Six grass species were established in 1968 in rows within a seeding of alfalfa (Medicago sativa L.) at Arlington, Wisconsin. The mixtures were harvested two, three, or four times annually at two stubble heights, 4 and 10 cm, during 1969 and 1970. Alfalfa was eliminated by spraying with a selective herbicide during autumn of 1970. Grasses were then evaluated for stand persistence and dry matter yields during the first growth of 1971.Orchardgrass (Dactylis glomerata L.), reed canarygrass (Phalaris arundinacea L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
2
1

Year Published

1977
1977
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 0 publications
4
34
2
1
Order By: Relevance
“…Many experiments have evaluated aspects of grasslegume mixtures, starting in the 1940s (Åberg et al, 1943;Comstock and Law, 1948;Chamblee, 1958). Some species like orchardgrass (Dactylis glomerata L.) may compete effectively against alfalfa and dominate mixtures (Hamilton et al, 1969;Smith et al, 1973;Weil, 1988). For example, mixtures can exhibit more even seasonal growth distribution due to legumes compensating for slower grass growth in summer (Åberg et al, 1943;Chamblee, 1958;Sleugh et al, 2000).…”
Section: Evaluation Of Alfalfa-tall Fescue Mixtures Across Multiple Ementioning
confidence: 99%
See 1 more Smart Citation
“…Many experiments have evaluated aspects of grasslegume mixtures, starting in the 1940s (Åberg et al, 1943;Comstock and Law, 1948;Chamblee, 1958). Some species like orchardgrass (Dactylis glomerata L.) may compete effectively against alfalfa and dominate mixtures (Hamilton et al, 1969;Smith et al, 1973;Weil, 1988). For example, mixtures can exhibit more even seasonal growth distribution due to legumes compensating for slower grass growth in summer (Åberg et al, 1943;Chamblee, 1958;Sleugh et al, 2000).…”
Section: Evaluation Of Alfalfa-tall Fescue Mixtures Across Multiple Ementioning
confidence: 99%
“…For example, nitrogen uptake from soil by grasses and possible N immobilization by the microbial community could help stimulate N fixation and associated legume growth (Craig et al, 1981;Brophy et al, 1987;Nyfeler et al, 2011). Smith et al (1973) found that if tall fescue was cut at a short stubble height (4 cm) and only harvested twice a year, it was almost eliminated from alfalfa mixtures likely due to shading. Harvest interval also can affect grass-legume balance.…”
Section: Herbage Accumulationmentioning
confidence: 99%
“…Persistence of perennial grasses is defined as the ability of each tiller to produce on offspring annually such that members of the population replace themselves (Edwards & Chapman, ). Many studies use either tiller density (Raese & Decker, ; Volesky & Anderson, ) or per cent ground cover (Brink et al., ; Smith, Jaques, & Balasko, ) to determine the effects of various treatments on the persistence of swards. It is also known, however, that tiller density alone is not always related to the yield of swards (Davies, ).…”
Section: Introductionmentioning
confidence: 99%
“…Smooth bromegrass is used for hay and pasture throughout temperate North America [9]. It is an upright-growing perennial that spreads by rhizomes to produce a dense sod [10]. Vogel et al [11] summarized results from harvest management studies on smooth bromegrass and concluded that forage yields are maximized when the first harvest is after heading and subsequent harvests are infrequent.…”
Section: Introductionmentioning
confidence: 99%
“…Knievel et al [12] found that the highest seasonal herbage yields and best stands of smooth bromegrass in Wisconsin occurred when the first crop was cut at early anthesis. Smith et al [10] reported that stands of smooth bromegrass, growing with alfalfa, were nearly eliminated within three years when they were cut three times annually at a cutting height of 4 cm.…”
Section: Introductionmentioning
confidence: 99%